Enhancing desalination performance and antifouling properties of thin film composite nanofiltration membrane via polyacrylic acid incorporating - Ibtissem Ounifi; Ali Boubakri; Sarra Elgharbi; Ali Rebhi; Olfa Bechambi; Amor Hafiane (Results in Chemistry)
This study reports the development of novel polyamide thin-film composite (TFC) nanofiltration (NF) membranes with enhanced antifouling properties. The membranes were fabricated via interfacial polymerization between piperazine (PIP) and trimesoyl chloride (TMC) on a cellulose acetate (CA) ultrafiltration support membrane. A key innovation involved the in-situ incorporation of polyacrylic acid (PAA) into the polyamide selective layer by dispersing it within the aqueous PIP monomer solution. The synthesized membranes underwent comprehensive characterization to elucidate their surface morphology, topography, and hydrophilicity. Additionally, the permeability and separation properties of membranes were evaluated. The results revealed that incorporating PAA into the TFC-NF membranes significantly increased surface roughness and hydrophilicity compared to reference membranes without PAA. The effect of PAA concentration on water permeability was investigated. Interestingly, water permeability increased from 8.5 LMH/bar to 17.9 LMH/bar with increasing PAA concentration from 0 wt% to 0.7 wt%. The order of salt rejection followed the trend: Na2SO4 > MgSO4 > MgCl2 > NaCl, which can be attributed to the introduction of negative charges of the modified membranes. Notably, the TFC membrane containing 0.5 wt% PAA exhibited the highest salt rejection, achieving 99.65 % rejection for Na2SO4 and 70.12 % rejection for NaCl. The antifouling properties of the TFC membranes were evaluated by monitoring their flux decline during bovine serum albumin (BSA) protein solution filtration. The incorporation of PAA into the polyamide layer of the TFC-NF membranes demonstrably improved their fouling resistance due to the increased negative charge, which repels negatively charged foulants like BSA.